Enhanced recovery after surgery programmes in older patients undergoing hepatopancreatobiliary surgery: what benefits might prehabilitation have?. (March 2021) - Bongers, Bart C.; Dejong, Cornelis H.C.; den Dulk, Marcel
Abstract: Due to an aging population and the related growing number of less physically fit patients with multiple comorbidities, adequate perioperative care is a new and rapidly developing clinical science that is becoming increasingly important. This narrative review focuses on enhanced recovery after surgery (ERAS®) programmes and the growing interest in prehabilitation programmes to improve patient- and treatment-related outcomes in older patients undergoing hepatopancreatobiliary (HPB) surgery. Future steps required in the further development of optimal perioperative care in HPB surgery are also discussed. Multidisciplinary preoperative risk assessment in multiple domains should be performed to identify, discuss, and reduce risks for optimal outcomes, or to consider alternative treatment options. Prehabilitation should focus on high-risk patients based on evidence-based cut-off values and should aim for (partly) supervised multimodal prehabilitation tailored to the individual patient's risk factors. The program should be executed in the living context of these high-risk patients to improve the participation rate and adherence, as well as to involve the patient's informal support system. Developing tailored (multimodal) prehabilitation programmes for the right patients, in the right context, and using the right outcome measures is important to demonstrate its potential to further improve patient- and treatment-related outcomes following HPB surgery.